Changes in Oxidative Stress and Intestinal Permeability during Pregnancy in Women with Gestational Diabetes Mellitus Treated with Metformin or Insulin and Healthy Controls: A Randomized Controlled Trial - Andrea Fernández-Valero; Nerea Peña-Montero; Fuensanta Lima-Rubio; Carolina Gutiérrez-Repiso; Teresa María Linares-Pineda; María José Picón-César; Raquel Sancho-Marín; Francisco J. Tinahones; Sonsoles Morcillo; María Molina-Vega (MDPI AG, 2023)
Both oxidative stress and intestinal permeability are increased in hyperglycemic situations and have been shown to be reduced by metformin in type 2 diabetes mellitus (T2DM) patients. The aim of this study was to elucidate the effect of metformin on oxidative stress and intestinal permeability in women with gestational diabetes mellitus (GDM) treated with metformin compared to those treated with insulin and healthy controls. A total of 120 women were included from August 2016 to February 2022: 41 received metformin (MET group), 38 received insulin (INS group), and 41 were healthy controls. Baseline and antenatal visits were carried out at 25.4 ± 4.8 and 36.1 ± 0.8 weeks of pregnancy, respectively. Advanced oxidation protein products (AOPPs), total antioxidant capacity (TAC), and zonulin levels were measured at every visit. Zonulin levels from baseline to prepartum visit increased significantly in both healthy controls (0.6 ± 0.9 to 1.2 ± 1.7 ng/mL, p = 0.004) and the INS group (0.4 ± 0.3 to 0.6 ± 0.5 ng/mL, p = 0.034) but did not significantly change in the MET group (0.4 ± 0.4 to 0.5 ± 0.4 ng/mL, p = 0.202). However, TAC and AOPP levels significantly increased in women with GDM, both in the INS and MET groups but not in the healthy controls. In conclusion, in our population, metformin has been shown to avoid an increase in intestinal permeability but failed to avoid an increase in oxidative stress related to hyperglycemia.